A Navajo saga - Bennett, Kay; Bennett, Russ (Naylor Co. San antonia, Texas, 1969)
The history of a Navajo family from 1846 to 1870 as they fought to maintain their homelands and dignity against the white man.
Keywords: New Fiction. -- of North America Southwest